Uma estrategia para alocação eficiente de recursos móveis utilizando sistema fuzzy para um esquema de planejamento e provimento de QoS - DIAS, Suzane Alfaia (Universidade Federal do Pará, 2019)
With mobile data growth and rapid urbanization trends, there will be an extremely high density of wireless communication links in cities, therefore users expect an environment where they can access the Internet to their devices anytime, anywhere. Due to CAPEX/OPEX problems, a small cell deployment is not an economical strategy in scenarios of intense data tra_c, so the use of UAVs to improve network coverage and performance becomes feasible. In order to improve the Quality of Service of the network, a computational system was proposed to perform decision making that receives as input network information such as network throughput, packet loss rate and delay, and returns to network quality for that speci_c type of network. application. The system as a whole veri_es the necessity or not of using Unmanned Aerial Vehicles (UAVs) to improve the quality of the network and the coverage of the area of greatest demand. If UAVs are required, they are shifted to the areas of greatest demand. Otherwise, the UAVs remain in the base station. Through the proposed method there were signi_cant improvements in the Quality of Service (QoS) of the network, allowing a reduction in packet loss and delay, and an increase in the network throughput rate.